A depth-of-interaction encoding PET detector module with dual-ended readout using large-area silicon photomultiplier arrays. (14th December 2018) - Du, Junwei; Bai, Xiaowei; Cherry, Simon R
Abstract: The performance of a depth-of-interaction (DOI) encoding PET detector module with dual-ended readout of LYSO scintillator arrays using large-area SiPM arrays was evaluated. Each SiPM array, with a surface area of 50.2 × 50.2 mm 2, consists of 12 × 12 C-series SiPMs from SensL (SensL, Inc). The LYSO array, with a total size of 46 × 46 mm 2 and a pitch size of 1.0 mm, consists of a 46 × 46 array of 0.945 × 0.945 × 20 mm 3 polished LYSO crystals, separated by Toray reflector. Custom front-end electronics were designed to reduce the 288 SiPM signals of one detector module to nine signals, eight for position information and 1 for timing information. Schottky diodes were used to block noise from SiPMs that did not detect a significant number of scintillation photons following a gamma interaction. Measurements of noise, signal, signal-to-noise ratio, energy resolution and flood histogram quality were obtained at different bias voltages (26.0 to 31.0 V in 0.5 V intervals) and at two temperatures (5 °C and 20 °C). Clear acrylic plates, 2.0 mm thick, were used as light guides to spread the scintillation photons. Timing resolution, depth of interaction resolution, and the effect of event rate on detector performance were measured at the bias voltage determined to be optimal for the flood histograms. Performance obtained with and without the noise-blocking Shottky diodes was also compared. The results showed that all crystals in the LYSO array can be clearly resolved, and performance improved when using diodes to block noise, and at the lower temperature. The average energy resolution, flood histogram quality, timing resolution and DOI resolution were 23.8% ± 2.0%, 1.54 ± 0.17, 1.78 ± 0.09 ns and 2.81 ± 0.13 mm respectively, obtained at a bias voltage of 30.0 V and a temperature of 5 °C using the diode readout method. The event rate experiments showed that the flood histogram and energy resolution of the detector were not significantly degraded for an event rate of up to 150 000 counts s −1 .